2018
DOI: 10.3389/fgene.2018.00627
|View full text |Cite
|
Sign up to set email alerts
|

Association of Copy Number Variation at Intron 3 of HMGA2 With Navel Length in Bos indicus

Abstract: Navel injuries caused by friction against the pasture can promote infection, reproductive problems and costly treatments in beef cattle raised in extensive systems. A haplotype-based genome-wide association study (GWAS) was performed for visual scores of navel length at yearling in Nellore cattle (Bos indicus) using data from 2,016 animals and 503,088 single nucleotide polymorphism (SNP) markers. The strongest signal (p = 1.01 × 10-9) was found on chromosome 5 spanning positions 47.9–48.2 Mbp. This region cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…HMGA2 polymorphism had earlier been found to be associated with the difference in body stature in mice (pygmy size) (Zhou et al, 1995), humans (oversize) (Ligon et al, 2005) and cattle (Pryce et al, 2011). Recently, the intronic copy number variation (CNV) of this gene has also been associated with navel length in Nellore cattle (Aguiar et al, 2018).The analysis of the annotated genes in these ROH regions of dairy and draft breeds also indicated that Kangayam was more resistant to diseases/had higher immunity (selection sweeps in LYZL1, SVIL and GPX4) and stress tolerant (CCT4). Whereas, dairy breeds had selection sweeps in key genes governing milk production (PTGFR, CSN1S1, CSN2, CSN1S2, and CSN3).…”
Section: Genomic Regions Within Overlapping Rohmentioning
confidence: 99%
“…HMGA2 polymorphism had earlier been found to be associated with the difference in body stature in mice (pygmy size) (Zhou et al, 1995), humans (oversize) (Ligon et al, 2005) and cattle (Pryce et al, 2011). Recently, the intronic copy number variation (CNV) of this gene has also been associated with navel length in Nellore cattle (Aguiar et al, 2018).The analysis of the annotated genes in these ROH regions of dairy and draft breeds also indicated that Kangayam was more resistant to diseases/had higher immunity (selection sweeps in LYZL1, SVIL and GPX4) and stress tolerant (CCT4). Whereas, dairy breeds had selection sweeps in key genes governing milk production (PTGFR, CSN1S1, CSN2, CSN1S2, and CSN3).…”
Section: Genomic Regions Within Overlapping Rohmentioning
confidence: 99%
“…Other mutations, including regulatory mutations in HELB that modify its expression pattern, or mutations in other genes such as HMGA2, could also affect tropical adaptation. Recently, a tandem repeat that includes the third and fourth introns of HMGA2 has been associated with navel score and with visual scores of precocity and muscling in Nellore cattle [53]. We show that the mutations in HELB and the HMGA2-CNVR can be inherited independently, which means that they can potentially affect different phenotypes.…”
Section: Discussionmentioning
confidence: 72%
“…(48,074,233-48,080,443 bp) was reported to affect the third and fourth introns of HMGA2 in Nellore cattle and to be associated with navel length (similar to sheath score) at yearling (Fig. 2c) [53]. Taken together, these results indicate this 430-kb selective sweep is relevant for selective breeding programs aimed at improving adaptation of cattle to tropical conditions.…”
Section: Genomic Regions Under Selection In European Taurine and Asiamentioning
confidence: 65%
See 2 more Smart Citations